2008
DOI: 10.5751/es-02616-130230
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Relational Concept of Uncertainty: about Knowing Too Little, Knowing Too Differently, and Accepting Not to Know

Abstract: Uncertainty of late has become an increasingly important and controversial topic in water resource management, and natural resources management in general. Diverse managing goals, changing environmental conditions, conflicting interests, and lack of predictability are some of the characteristics that decision makers have to face. This has resulted in the application and development of strategies such as adaptive management, which proposes flexibility and capability to adapt to unknown conditions as a way of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
262
0
24

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(307 citation statements)
references
References 51 publications
1
262
0
24
Order By: Relevance
“…It is characterized by multiple variables and levels, and it has the capacity to change and to adapt through time applying feedbacks and adaptation mechanisms that are particular to each system. Adopting these ideas has profound implications for how decisions are made, since humans have the capacity of adapting to new conditions and learning new ways of acting (Brugnach and Pahl-Wostl, 2007). Under this framework of analysis managing solutions cannot any longer be sought as independent from what those who participate value and believe to be important (Bouwen and Taillieu, 2004;Schusler et al, 2003).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by multiple variables and levels, and it has the capacity to change and to adapt through time applying feedbacks and adaptation mechanisms that are particular to each system. Adopting these ideas has profound implications for how decisions are made, since humans have the capacity of adapting to new conditions and learning new ways of acting (Brugnach and Pahl-Wostl, 2007). Under this framework of analysis managing solutions cannot any longer be sought as independent from what those who participate value and believe to be important (Bouwen and Taillieu, 2004;Schusler et al, 2003).…”
Section: 2mentioning
confidence: 99%
“…In contrast to factual scientific knowledge, this knowledge is tacit and it is not explicitly expressed except through practices. Moreover, knowledge is also influenced by the views and preferences of the decision maker in relation to those of other actors with whom the decision maker interacts in the context of a specific situation (Schusler et al, 2003;Brugnach et al, 2008). Thus knowledge is situated and it reflects the ability of people to interact with the natural and social systems.…”
Section: Different Types Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty, defined as an incomplete understanding of a system to be managed (Brugnach et al 2008) limits our knowledge about potential drought impacts and its probability of occurrence. Quantified uncertainty handles risk as a combination of the "true" probability of a natural hazard and its impacts (Blaikie 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature, however, we found that substantive uncertainty has been a topic mainly in policy analysis and operational research (Morgan andHenrion 1990, Walker et al 2003), while process uncertainty is discussed mainly in the field of policy networks and process management (Kickert et al 1997, Rhodes 1997. Studies that explicitly address both process and substantive uncertainty (Wynne 1992a, Koppenjan and Klijn 2004, Brugnach et al 2008 are rare. We suggest that more research into the interaction between the handling of different types of uncertainty is warranted.…”
Section: Focus On Uncertainty Handlingmentioning
confidence: 99%